Periodontal Pathogens Promote Oral Squamous Cell Carcinoma by Regulating ATR and NLRP3 Inflammasome - Yao, Yufei; Shen, Xin; Zhou, Maolin; Tang, Boyu (Frontiers in Oncology, 2021)
Periodontitis is closely related to oral cancer, but the molecular mechanism of periodontal pathogens involved in the occurrence and development of oral cancer is still inconclusive. Here, we demonstrate that in vitro the cell proliferation ability and S-phase cells of the periodontitis group (P+) significantly increased, but the G1 cells were obviously reduced. The animal models with an in situ oral squamous cell carcinoma and periodontitis-associated bacteria treatment were constructed and micro-CT showed that the alveolar bone resorption of mice in the P+ group (75.3±4.0 μm) increased by about 53%, compared with the control group (48.8±1.3 μm). The tumor mass and tumor growth rate in the P+ group were all higher than that in the blank control group. HE staining of isolated tumor tissues showed that large-scale flaky necrosis was found in the tumor tissue of the P+ group, with lots of damaged vascular profile and cell debris. IHC of isolated tumor tissues showed that the expression of Ki67 and the positive rate of CyclinD1 was significantly higher in tumor tissues of the P+ group; The qRT-PCR results of the expression of inflammatory cytokines in oral cancer showed that periodontitis-associated bacteria significantly upregulated the IL-6, TNF-α, IL-18, ASC (up to 6 times), and caspase-1 (up to 4 times), but it downregulated NF-κΒ, NLRP3 and IL-1β (less than 0.5 times). In addition, the volume of spleen tissue and the number of CD4+T, CD8+T and CD206+T cells in the P+ group increased significantly. IHC and western blotting in tumor tissues showed that expression levels of γ-H2AX, p-ATR, RPA32, CHK1, RAD51 were up-regulated, and the phosphorylation level of CHK1 (p-chk1) were down-regulated. Together, we identify that the periodontitis related bacteria can initiate the overexpressed NLRP3, activate upstream signal molecules of ATR-CHK1, promoting the tumor growth and proliferation. It is expected to develop a new molecular mechanism between periodontitis related bacteria and OSCC.